EDUKASI RAMAH LINGKUNGAN : PERSPEKTIF GENDER DALAM AGRIBISNIS EKOLOGIS - KUSUMO, RANI ANDRIANI BUDI; CHARINA, ANNE; SUKAYAT, YAYAT (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
The purpose of this study were to: 1) analyze the role of gender differences in the response of consumers as well as eco-friendly behavior; 2) Develop a model of eco-friendly education to encourage changes in society behavior. This research was conducted by survey techniques. Respondents in this study were consumers who shop through the 'Small Market' which numbered 60 people. Descriptive analysis and t test are used to answer the purposes of this study. The results showed a significant difference between men and women in collective values, affective response, conative response and eco friendly behavior.To construct eco friendly behavior requires the responsibilities of all parties. , Governments, producers, consumers, educational institutions and the media have their respective roles to be able to raise awareness of eco friendly behavior.